Pendampingan Pembelajaran Jurnalistik untuk Meningkatkan Kemampuan Menulis Berita Generasi Muda di Desa Terung Kulon, Krian, Sidoarjo - Mas Ummu Chasbiyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
A key issue in this initiative is the low level of media literacy and news writing skills among the younger generation in Terungkulon Village, as evidenced by students’ inability to analyze, filter, and present information objectively in the face of rampant fake news. Participatory Action Research (PAR), which requires active participant involvement, was employed to conduct journalism mentoring activities aimed at addressing this issue. Observation and interviews were used as data collection methods, while basic journalism resources, news analysis, and hands-on news writing exercises were employed to carry out the activities. The results of the exercises showed an improvement in students’ understanding of news structure, methodical information processing, and independent news writing. Critical thinking skills, self-confidence, and knowledge of journalistic ethics all improved. The main conclusion from this activity is that journalism education is effective in improving media literacy and writing skills, and is capable of fostering active learning as a source of knowledge that is critical, educational, and engaging for the general public.